2017
DOI: 10.2460/ajvr.78.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyaluronan alone or in combination with chondroitin sulfate and N-acetyl-d-glucosamine on lipopolysaccharide challenge-exposed equine fibroblast-like synovial cells

Abstract: OBJECTIVE To investigate effects of hyaluronic acid (HA) or HA combined with chondroitin sulfate (CS) and N-acetyl-d-glucosamine (NAG) by use of a lipopolysaccharide (LPS) in vitro method. SAMPLE Monolayer cultures of synovial cells from 4 adult horses. PROCEDURES Synovial cell cultures were untreated or treated with HA alone or HA-CS-NAG for 24 hours, subsequently unchallenged or challenge-exposed with 2 LPS concentrations (20 and 50 ng/mL) for 2 hours, and retreated with HA or HA-CS-NAG for another 24 hours.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Synovial cell cultures exposed to lipopolysaccharide treatment, instead, were reported in the literature as a model to study the protective and anti-inflammatory effects of HA alone or in combination with CS and GlcN [34, 35]. In addition, through the NF-κB activation and IL-8 production, the synovial cells have been used to evaluate the anti-inflammatory response of food supplements with other potentially bioactive molecules (e.g., HA, collagen peptides, Boswellia serrata , devil’s claw, or curcumin).…”
Section: Discussionmentioning
confidence: 99%
“…Synovial cell cultures exposed to lipopolysaccharide treatment, instead, were reported in the literature as a model to study the protective and anti-inflammatory effects of HA alone or in combination with CS and GlcN [34, 35]. In addition, through the NF-κB activation and IL-8 production, the synovial cells have been used to evaluate the anti-inflammatory response of food supplements with other potentially bioactive molecules (e.g., HA, collagen peptides, Boswellia serrata , devil’s claw, or curcumin).…”
Section: Discussionmentioning
confidence: 99%
“…The LMW-HA group, but not the HMW-HA group, showed a lower concentration of SF TNF-α and IL-6 than the TA group. Other studies reported that equine fibroblast-like synovial cells exposed to LPS showed increased concentrations of IL-6, but the cells treated with HMW-HA had significantly better viability and morphology scores and lower concentrations of IL-6 than the untreated LPS-exposed cells [33]. Furthermore, HMW-HA can suppress the LPS-activated PI3K/Akt pathway, leading to the downregulation of nuclear factor (NF)-κB with decreased IL-6 production through an interaction with intercellular adhesion molecule 1 [34].…”
Section: Discussionmentioning
confidence: 99%
“…GlcN can be obtained through the extraction of chitin from crustacean shells followed by both alkaline or acid hydrolyzes or by de novo chemical synthesis [5,9], and it is commercialized as stabilized salt of glucosamine or glucosamine sulfate [5]. Despite that, CS and GlcN are combined in pharmaceutical preparations and in food supplements to be orally administered as anti-osteoarthritis active principles even in long-term therapy [15]. The EULAR and the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis and Musculoskeletal Disease (ESCEO) have recommended daily dosages of CS and GlcN between 800 and 1200 mg and between 1250 and 1500 mg, respectively [4,8].…”
Section: Introductionmentioning
confidence: 99%